New taxonomic and faunistic data on Liocranidae (Arachnida: Araneae) of West Palaearctic), with nine new species of Mesiotelus Simon, 1897 - Zamani, Alireza; Fomichev, Alexander A.; Naumova, Maria; Kaya, Rahşen S.; Marusik, Yuri M. (Zootaxa, 2024)
New taxonomic data and distribution records on liocranid spiders in the West Palaearctic are provided. Nine species of Mesiotelus Simon, 1897 are described as new to science: M. alanyensis Zamani, Fomichev, Kaya & Marusik, sp. nov. (female; Türkiye), M. bosmansi Zamani, Fomichev & Marusik, sp. nov. (female; Türkiye), M. confusus Zamani, Fomichev, Naumova & Marusik, sp. nov. (male, female; Bulgaria, Greece, Türkiye), M. damavandicus Zamani, Fomichev & Marusik, sp. nov. (female; Iran), M. kravetsi Fomichev, Zamani & Marusik, sp. nov. (male; Russia: Dagestan), M. mediterraneus Zamani, Fomichev & Marusik, sp. nov. (female; Türkiye), M. sistanus Zamani, Fomichev & Marusik, sp. nov. (female; Iran), M. tadzhikus Zamani, Fomichev & Marusik, sp. nov. (female; Tajikistan), and M. turanicus Zamani, Fomichev & Marusik, sp. nov. (female; Tajikistan). Due to the misidentification of the first specimen described as the male of M. scopensis Drensky, 1935, all records of this species from Bulgaria, Greece, and Türkiye in fact belong to a different species, which is described here as M. confusus sp. nov. Considering the revised definition of M. scopensis, M. deltshevi Naumova, 2020 syn. n. and M. caucasicus Zamani & Marusik, 2021 syn. n. are proposed as its junior synonyms, and to ensure nomenclatural stability, a neotype is designated for it. The previously unknown females of Agroeca angirasu Zamani & Marusik, 2021 and M. patricki Zamani & Marusik, 2021 are described. The nomen Mesiotelus mersinensis Demircan Aksan, 2023 is here declared to be unavailable. The following species are newly recorded from the listed countries: A. angirasu from Azerbaijan, M. scopensis from Azerbaijan and Georgia, and M. cyprius Kulczyński, 1908 from Türkiye. Three of the previous Iranian records of M. scopensis Drensky, 1935 and the Iranian and Turkmen records of M. kulczynskii Charitonov, 1946 are found to be based on misidentifications. Additionally, the vulva of Sestakovaia annulipes (Kulczyński, 1897) is illustrated for the first time.